Mechanism evaluation of the interactions between flavonoids and bovine serum albumin based on multi-spectroscopy, molecular docking and Q-TOF HR-MS analyses. (15th July 2016) - Fu, Ling; Sun, Yiqun; Ding, Lina; Wang, Yangyang; Gao, Zhen; Wu, Zhen; Wang, Shaomin; Li, Wen; Bi, Yuefeng
Highlights: Q-TOF HR-MS were used to research the interaction between flavonoids and BSA. Different substituent groups such as methoxyl on the A, B ring of flavonoid. Fluorescence suggested the chain structure of BSA was altered after binding. Fluorescence and docking suggested substituent locations would affect interaction. Abstract: The mechanism of interactions between a flavonoid glycoside (linarin) and 6 flavonoids with various hydroxyl and methoxyl substituents (luteolin, apigenin, acacetin, tricin, 5, 3′, 4′-trihydroxy-6, 7-dimethoxyflavone, and 5, 7, 4′-trihydroxy-6, 3′, 5′-trimethoxyflavone) and bovine serum albumin (BSA) were investigated by multi-spectroscopy, molecular docking, and quadrupole (Q)-time of flight (TOF) high resolution (HR) mass spectrometry (MS). Fluorescence spectra and molecular docking predicted that each of the flavonoids had only one probable binding site inside the hydrophobic cleft of BSA. The binding constants appeared to correlate positively with the number of hydroxyl groups, and negatively with the number of methoxyl groups. In addition, hydroxyls on ring B bound more easily with BSA than those on ring A. The change in conformation of BSA after binding suggested that the quenching mechanism was static quenching combined with nonradiative energy transfer. The results of Q-TOF HR-MS were consistent with fluorescence quenching and molecular docking.